Efficacy and safety of fire needle combined with cupping for acute herpes zoster and postherpetic neuralgia: A protocol for systemic review and meta-analysis. Issue 50 (16th December 2022) - Huang, Shijie; Xu, Yipeng; Pan, Zhengqi; Li, Zimeng; Luo, Rui; Yu, Maogui; Li, Wuyu; Liu, Hanghang; Wu, Jie
Abstract : Background: Herpes zoster and post-herpetic neuralgia showed an increasing incidence during past two decades. Most of herpes zoster and post-herpetic neuralgia patients suffered from pain, anxiety, and depression. Fire needle combined with cupping is becoming a popular way to relieve the pain caused by herpes zoster and decrease the incidence of post-herpetic neuralgia. In this study, we aim to investigating the efficacy and safety of fire needle combined with cupping for the treatment of acute herpes zoster and postherpetic neuralgia (PHN). Methods: The literature search will be carried out in following databases: PubMed/MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, Chinese Biomedical Literature Database and Wanfang Data. Published and unpublished controlled trials compared fire needle combined with cupping to other treatments for acute herpes zoster or PHN will be included. Data from eligible studies will be extracted by 2 independent reviewers. Different scales will be used to assess the risk of bias based on the study design. Pain intensity and PHN are primary outcomes. The final effect size will be reported using 95% confidence interval at 0.05 significance level. Discussion: This review will provide certain evidence to compare the efficacy and safety of combined acupuncture and cupping with guideline recommended drug or nerve block therapy for the treatment of herpes zoster and post-herpetic neuralgia. It will potentially provide more clinical suggestions and guidelines for health care professionals, policymakers, and researchers.